A Revelação nos Concílios de Trento e Vaticano II - Ribeiro, Ari Luís do Vale (Teocomunicação, 2006)
This article deals with the Revelation of God in the Council of Trent and the Second Vatican Council. First the Author focuses the Revelation in the Trentine Council and in the two Vatican Councils. After he shows the necessity of explicitation by the Holy Seat about the reveald truths, in order to understand them actually, paying attention to the sensus fidei and the so called signs of the time.